2011
DOI: 10.2500/ajra.2011.25.3701
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Esmolol Infusion Improves Surgical Fields during Sevoflurane-Anesthetized Endoscopic Sinus Surgery: A Double-Blind, Randomized, Placebo-Controlled Trial

Abstract: Esmolol-induced relative hypotension and bradycardia during endoscopic sinus surgery achieves significantly improved SFs relative to saline control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 25 publications
2
18
1
Order By: Relevance
“…Our findings show the similar positive effects on hemodynamics during surgery and recovery, but remifentanil had better condition during surgery and recovery. [17] All these findings show that, however, remifentanil had similar effects on hemodynamics compare to different anesthetic agents but reported that remifentanil as an opioid with the shortest onset and offset due to its metabolism by a specific tissue and plasma esterase and have better surgical field condition.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings show the similar positive effects on hemodynamics during surgery and recovery, but remifentanil had better condition during surgery and recovery. [17] All these findings show that, however, remifentanil had similar effects on hemodynamics compare to different anesthetic agents but reported that remifentanil as an opioid with the shortest onset and offset due to its metabolism by a specific tissue and plasma esterase and have better surgical field condition.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] FESS is better to be performed under controlled hypotensive technique (mean arterial pressure [MAP] between 60 and 70 mmHg); this can improve surgical field and decrease the operation time. [ 2 ] Several medications have been used to provide controlled hypotension such as inhalational volatile agents,[ 3 ] remifentanil,[ 4 ] clonidine,[ 5 ] dexmedetomidine,[ 6 ] nitroglycerine,[ 7 ] esmolol,[ 8 ] intravenous lidocaine,[ 9 ] and magnesium sulfate. [ 10 11 12 ]…”
Section: Introductionmentioning
confidence: 99%
“…15 Beta-blockers, on the other hand, have been shown to be of advantage because they decrease blood pressure by lowering cardiac output rather than systemic vascular resistance. 14 …”
Section: Introductionmentioning
confidence: 99%